A colorimetric and ratiometric fluorescent probe for ClO− targeting in mitochondria and its application in vivo1. Issue 8 (28th February 2015) - Xiao, Hongde; Li, Jianhui; Zhao, Jin; Yin, Gui; Quan, Yiwu; Wang, Jie; Wang, Ruiyong
<x xml:space="preserve">Abstract</x> A colorimetric and ratiometric fluorescent probe PMN–TPP for imaging mitochondrial ClO− was prepared. The probe performed well in detecting ClO− in the mitochondria of living RAW264.7 macrophage cells and a living nude mouse.